1996
DOI: 10.1136/vr.139.6.130
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of lameness in dairy cattle: the influence of cubicles and indoor and outdoor walking surfaces

Abstract: A survey of cubicles and indoor and outdoor walking surfaces on 37 farms served by four veterinary practices in Somerset, Cheshire, Wirral and west. Wales was carried out in 1989 to 1991. A study of the space requirements of Friesian/Holstein cows at pasture showed that they required approximately 240 cm x 120 cm lying space and a further 60 cm lunging space for rising. By these standards, 87 per cent of the cubicles were too short and 50 per cent were too wide or too narrow. Over 1500 observations on cows lyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 9 publications
2
60
1
Order By: Relevance
“…Claw horn lesions are a major cause of lameness. The incidence of such lesions was higher for cows housed on hard concrete floors (Bergsten and Frank, 1996;Faull et al, 1996), and for cows housed in cubicles than for cows in straw yards (Livesey et al, 1998). Conditions in straw yards are less conducive to hoof wear: cattle spend more time lying down and the floor surface is dry and resilient (Phillips and Schofield, 1994).…”
Section: Hygiene and Healthmentioning
confidence: 99%
“…Claw horn lesions are a major cause of lameness. The incidence of such lesions was higher for cows housed on hard concrete floors (Bergsten and Frank, 1996;Faull et al, 1996), and for cows housed in cubicles than for cows in straw yards (Livesey et al, 1998). Conditions in straw yards are less conducive to hoof wear: cattle spend more time lying down and the floor surface is dry and resilient (Phillips and Schofield, 1994).…”
Section: Hygiene and Healthmentioning
confidence: 99%
“…Narrow, uncomfortable cubicles (Philipot et al 1993) have been suggested to be important influencing factors on lameness incidence. In the study by Faull et al (1996) suggested that the height of the kerb should be no more than 15 cm. Variations in floor level have been suggested as a possible risk factor for claw horn lesions (Philipot et al 1993).…”
Section: Cubicle Designmentioning
confidence: 99%
“…Dairy cows need to optimize their lying time, as disturbed rest may affect milk production by reducing the secretion of growth hormone (Munksgaard and Løvendahl 1993). Reduced lying time is also associated with hoof disease and lameness (Singh et al 1993, Leonard et al 1994, Faull et al 1996, Sonck et al 1999). In free stall or cubicle housing, poorly designed stalls lead to reduced stall occupancy (O'Connell et al 1993), and the type of flooring in the stall may affect time spent lying down (Natzke et al 1982, Herlin 1997, Sonck et al 1999.…”
Section: Introductionmentioning
confidence: 99%